British Colonial Education in the Indian Subcontinent (1757-1858): Attitude of Muslims - Momen, Abdul; Ebrahimi, Mansoureh; Yusoff, Kamaruzaman (Journal of Islamic Thought and Civilization, 2024)
This article investigates the British colonial education imparted in the Indian Subcontinent during the priod 1757-1858, keeping in view the Muslim perspective. The objective is to comprehend the complex and diverse ways in which Muslims responded to British education throughout the colonial era, which were influenced by revolutionary and reactionary movements ignited by British domination. Muslims developed a complicated relationship with colonial education as a result of tensions heightened by the repression of indigenous concerns and the disregard for the acquisition of Islamic values. This study aims to comprehend the purpose of British education in the Indian subcontinent, analyses competing Muslim ideologies surrounding colonial education, uncovers factors influencing Muslim attitudes toward education during the British rule, and also analyses the differences in how different groups of Muslims responded to British education throughout British colonialism. For this purpose, this study uses a qualitative research methodology to investigate historical sources and determine the factors contributing to the hostile and defensive views of Indian Muslims regarding colonial education. The findings demonstrate the complex effects of British colonial policies, underlining the conflicts brought about by the disregard for Islamic knowledge and the fallout from the Sepoy Revolution. The study depicts varying responses to western education and competing ideologies among Muslims in India and underscores the significance of placing Muslim views in the larger sociopolitical context of colonial India. It also emphasises how critical it is to comprehend Muslim viewpoints on colonial education to dispel myths and promote a nuanced awareness of the historical legacies that continue to influence educational practices in post-colonial cultures.